Formulasi Strategi Peningkatan Mutu Institut Agama Islam Negeri (IAIN) di Jawa Timur - Mutohar, Prim Masrokan (STIT Pringsewu, 2019)
AbstractThis study wants to examine the formulation of the strategy for improving the quality of IAIN in East Java which is focused on: (1) strengthening the academic field (core activities of Higher Education); and (2) Strengthening the supporting activities of Higher Education in improving the quality of IAIN. The development of science and technology in the global era that occurs at this time brings the impact of changes in human life and all the problems can be solved by the mastery of science and the development of technology. This condition requires IAIN in East Java to be able to respond positively and can improve quality and can respond to stakeholder needs and the development of science and technology positively. In order for the IAIN to be able to meet the demands and needs of stakeholders and play a dynamic role in global competition, it is necessary to formulate a strategy to improve the quality of the institution properly. The formulation of this strategy can be used as an effort to make strategic planning carried out in a planned, directed, intensive, effective, and efficient manner in the process of improving the quality of IAIN in the current global era